Handbook of anthropology in business - Denny, Rita Mary Taylor, 1956-; Sunderland, Patricia L. (Routledge, an imprint of Taylor & Francis Group, 2016)
"In recent years announcements of the birth of business anthropology have ricocheted around the globe. The first major reference work on this field, the Handbook of Anthropology in Business is a creative production of more than 60 international scholar-practitioners working in universities and corporate settings from high tech to health care. Offering broad coverage of theory and practice around the world, chapters demonstrate the vibrant tensions and innovation that emerge in intersections between anthropology and business and between corporate worlds and the lives of individual scholar-practitioners. Breaking from standard attempts to define scholarly fields as products of fixed consensus, the authors reveal an evolving mosaic of engagement and innovation, offering a paradigm for understanding anthropology in business for years to come."--Provided by publisher